Morphology modification of LiNi0.5Co0.2Mn0.3O2 by incorporating cotton textiles in lithium-ion capacitors - Truong, Phat; Sun, Quanwen; Tang, Wei; He, Rong; Zhou, Meng; Luo, Hongmei (Frontiers in Batteries and Electrochemistry, 2024)
To address the alerting issue of energy demand, lithium-ion capacitors (LICs) have been widely studied as promising electrochemical energy storage devices, which can deliver higher energy density than supercapacitors (SCs), and have higher power density with longer cycling life than lithium-ion batteries (LIBs). In this work, the active material lithium nickel cobalt manganese oxide LiNi0.5Co0.2Mn0.3O2 (NCM523) is grown on a cotton textile template and building a 3-dimensional (3D) integrity to improve capacitance and energy density of LICs by enhancing the interfacial ion-exchange process. With the 3D structure, the specific discharge capacitance is increased to 718.67 F g−1 at 0.1 A g−1 from that of non-textile NCM523 (265.97 F g−1), and remains a high capacitance of 254.48 Fg−1 at 10 A g−1 in the half-cell capacitors. In addition, the energy density can achieve up to 36.17 Wh kg−1 at the power density of 1,200 W kg−1 in the full-cell capacitor. The textile NCM can maintain an energy density of 28.26 Wh kg−1 at the current density of 10 A g−1 and power density of 6,000 W kg−1. Our results present promising applications of electrodes with the 3D porous structure for high energy density LICs.